2016
DOI: 10.5897/ajb2016.15332
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-mouth disease (FMD) prevalence and exposure factors associated with seropositivity of cattle in north-central, Nigeria

Abstract: This study was designed to determine the seroprevalence and risk factors associated with foot-andmouth disease (FMD) seropositivity in north central, Nigeria. A cross-sectional study was undertaken from February 2013 to April 2014 using 1206 sera from 150 herds collected by multi-stage and random sampling methods. Pre-tested questionnaire were also administered to participating farmers to collect information on the animal herd structure, movement pattern, management system and herds contact at watering points.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
(23 reference statements)
3
15
0
Order By: Relevance
“…This may also be due to the fact that adult animals are repeatedly exposed and in close contact with other animals in pastures and water points. Our results are similar to those published by Wungak, Olugasa, Ishola, Lazarus, and Ularamu (). These authors determined seroprevalence by age group in Nigeria and also obtained higher seroprevalence in adults than in young animals.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This may also be due to the fact that adult animals are repeatedly exposed and in close contact with other animals in pastures and water points. Our results are similar to those published by Wungak, Olugasa, Ishola, Lazarus, and Ularamu (). These authors determined seroprevalence by age group in Nigeria and also obtained higher seroprevalence in adults than in young animals.…”
Section: Resultssupporting
confidence: 93%
“…The presence of the four serotypes (A, O, SAT1 and SAT2) in the country could be due to the free cross‐border movement of animals in search of pastures and water points as well as uncontrolled trade in livestock between Chad, the Central African Republic, Sudan, Cameroon and Niger. Indeed, these four circulating serotypes (O, A, SAT1 and SAT2) have also been identified and not yet eradicated in countries bordering Chad (Bertram, Bravo, et al, ; Bertram, Delgado, et al, ; Habiela, Alamin, et al, ; Habiela, Ferris, et al, ; Kouato, Elliot, et al, ; Kouato, Souley, et al, ; Wungak et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is is consistent with results of previous survey for FMDV antibodies in Nigeria in which a seroprevalence of 75.11% was reported in a study conducted in cattle in Kwara State [34]. Also, seroprevalences of 64.3% and 70.98%, respectively, were reported in studies carried out in Plateau State [35,36] and 64.7% in a study conducted at the border states in Nigeria [21,37]. e similarities of findings of the present study with previous studies have shown that FMD is still an enzootic disease in Nigeria, and this could be attributed to the lack of FMD vaccination campaigns in Nigeria [21,37].…”
Section: Discussionsupporting
confidence: 92%
“…Also, seroprevalences of 64.3% and 70.98%, respectively, were reported in studies carried out in Plateau State [35,36] and 64.7% in a study conducted at the border states in Nigeria [21,37]. e similarities of findings of the present study with previous studies have shown that FMD is still an enzootic disease in Nigeria, and this could be attributed to the lack of FMD vaccination campaigns in Nigeria [21,37]. ere is unrestricted herds mobility, continuous contact, and intermingling of different cattle herds at water points, communal grazing areas, and porous borders.…”
Section: Discussionmentioning
confidence: 98%